Desenvolvimento e avaliação de um mecanismo rotativo para descompactação de solo - Rodrigues, Henrique Eguilhor (2021)
The present work sought to develop and evaluate a prototype mechanism that presents greater efficiency in soil mobilization, an alternative to scarifying and subsoiling implements, mainly aiming to reduce the traction effort and energy demand. The experiment was carried out in an area owned by the Federal University of Santa Maria, located in the city of Santa Maria/RS. The design used was randomized blocks, formed by 6 treatments in a 2x3 factorial scheme. This being composed of 2 mechanisms (prototype and scarifying shank) mounted on a mobile tool holder at 3 displacement speeds (1.30, 1.60 and 1.90 m s-1). The results show that the development of the prototype in the constructive scope was satisfactory, it performed the function for which it was designed without showing any damage, validating it with great potential for use, after improvements, and a promising method of unpacking. The prototype's geometry favored the reduction in the demand for force (-62.1%) and power (-67.7%) in the drawbar, however, fuel consumption behaved in an unstable way. The penetration of the prototype rods according to the displacement of the tractor did not provide greater levels of depth (-36.3%) and furrow width (-8.4%), resulting in an average smaller mobilized soil area (-36 .4%). After the operations, the soil area raised by the prototype was smaller (-26.2%), showing aptitude for conservation management. The prototype established a lower specific operational strength (-39.6%) and specific traction (-38.96%), however, external factors influenced them, providing such results, such as penetration of the rods in more superficial and less dense layers when compared the scarifying rod, in addition to the gigantic variability of the water content in the soil in the experimental area.